Study Productivity And Decomposition Litterfall In Sibolangit Forest, Deli Serdang To Support Field Trip Plantation Ecology - Tonggo Sinaga (Universitas Negeri Medan, 2015)
The research was conducted in mountain rain forest of Sibolangit, Deli Serdang, Northen Sumatera. The objectives of this research are to know litter fall productivity, decomposition and litterfall nutrients. Litterfall is the fallen leaves, twigs, flowers and fruits to forest-floor, which one of the input of nutrients to anorganic sril. This input is one of the nutrients cycling to forest ecosystem and the other form atmosfer and a lot of animals. Based on available data on 20 traps, litterfall productivity 5,91 gr/m2/week or 3073,2 kg/ha/year in high topography. Litterfall productivity 4,92gr/m2/week or 2558,4 kg/ha/year in low topography. Litterfall decomposition (lossed of weight) about 25,48% in 30 days ( 1 month ) for meranti ( Shorea sp ) and leaves of Ficus sp had lossed of weight about 8,09% in 30 days ( 1 month ). Ration C/N (Carbon-Nitrogen) litterfall and soil moisture made differrent litterfall decomposition (lossed of weight) Keywords : Productivity, Decomposition, Litterfall, Productivity.